Differential expression of microRNAs in adipose tissue after long-term high-fat diet-induced obesity in mice. - Dionysios V Chartoumpekis (Public Library of Science (PLoS), 2012)
Obesity is a major health concern worldwide which is associated with increased risk of chronic diseases such as metabolic syndrome, cardiovascular disease and cancer. The elucidation of the molecular mechanisms involved in adipogenesis and obesogenesis is of essential importance as it could lead to the identification of novel biomarkers and therapeutic targets for the development of anti-obesity drugs. MicroRNAs (miRNAs) have been shown to play regulatory roles in several biological processes. They have become a growing research field and consist of promising pharmaceutical targets in various fields such as cancer, metabolism, etc. The present study investigated the possible implication of miRNAs in adipose tissue during the development of obesity using as a model the C57BLJ6 mice fed a high-fat diet.C57BLJ6 wild type male mice were fed either a standard (SD) or a high-fat diet (HFD) for 5 months. Total RNA was prepared from white adipose tissue and was used for microRNA profiling and qPCR.Twenty-two of the most differentially expressed miRNAs, as identified by the microRNA profiling were validated using qPCR. The results of the present study confirmed previous results. The up-regulation of mmu-miR-222 and the down-regulation of mmu-miR-200b, mmu-miR-200c, mmu-miR-204, mmu-miR-30a*, mmu-miR-193, mmu-miR-378 and mmu-miR-30e* after HFD feeding has also been previously reported. On the other hand, we show for the first time the up-regulation of mmu-miR-342-3p, mmu-miR-142-3p, mmu-miR-142-5p, mmu-miR-21, mmu-miR-146a, mmu-miR-146b, mmu-miR-379 and the down-regulation of mmu-miR-122, mmu-miR-133b, mmu-miR-1, mmu-miR-30a*, mmu-miR-192 and mmu-miR-203 during the development of obesity. However, future studies are warranted in order to understand the exact role that miRNAs play in adipogenesis and obesity.